Quarterlife Crisis Pada Masa Dewasa Awal di Pekanbaru - Icha Herawati; Ahmad Hidayat (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
The transition from adolescents to adult challenges is different from the challenges of life in the previous development process. Towards the age of 25, individuals face a new life such as work, marital status, and mindset. The quarter-life crisis is a phenomenon that is common in individuals aged 20-30 years old. The crisis of a quarter of a century, that's how the term counts with individuals who attend 25 years. The quarter-life crisis experiences’ by individuals grew up. This research is descriptive quantitative research. The subjects in this study consist of 236 adults in Pekanbaru who attended for 20-30 years. The retrieval of data in this study uses the quarter-life crisis scale. The results showed that the early adult individual quarter-life crisis in Pekanbaru reached 43.22%, increasing the high category of 27.97%. The results showed the fact that factors affecting the quarterly life crisis estimated as gender, status, and occupation. The conclusions of this study show that adults in Pekanbaru who spend a quarter of life issued by women, are single and do not have jobs.